The Use of Spatial Statistics in Hydrography - Kielland, Peter; Dagbert, Michael (The International Hydrographic Review, 2015)
This paper describes ongoing efforts by the Canadian Hydrographic Service to devise geostatistical techniques for optimizing the nominal line spacing used on bathymetric surveys. This survey planning parameter has a great impact on both the cost of a survey and the confidence that a mariner can have in the resulting chart. Current methodology establishes initial line spacing quite subjectively. The main advantage of the geostatistical method being implemented is that it can estimate both depths and an estimate of their variance for all points within the survey area, regardless of whether they lie on or between sounding profiles. The geostatistical software under development (called "Hydrostat") evaluates the roughness of local bathymetry using available data. It then computes and displays the additional sounding coverage required to map the area to any desired level of confidence. The ideal line spacing for each small zone within the survey area is computed after specifying a maximum allowable standard deviation for interpolated depths lying between the sounding profiles. Developing algorithms for estimating the standard deviation of interpolated depths and ground truthing their accuracy forms the bulk of the work being done. While conceptually identical to the age old rules of thumb used to select and examine shoals, the geostatistical routines being developed can lead to more objective data quality standards and a more efficient deployment of survey resources.